PO1s in PRO6 more complaints are filed? - Inventor, Lailyn C.; Setias, Michael Ian; Sumodio, Candelaria D.; Unarce, Vincent
This study entitled "PO1's in PRO6: More complaints are filed? was conducted during the second tri-semester of the academic year 2006-2007 on the different PNP stations in Western Visayas. It determined the factors why more complaints are filed against the PO1s as compared to other rank assignments in PRO6. Thus, it will provide significant information regarding the causes of the various complaints filed by society against the PO1 of the PRO6 and the possible human resources management tools on how to reduce the number of complaints filed against them. This study considered the socio-demographic profile of the respondents like their age, sex, civil status, rank, length of service and annual income. It also involved factors under their work attitude such as their motivation to work, awareness of the standards of performance, observance of the standards of performance, gaps in work performance: and in human resources management factors which include training and discipline for the attainment of the goals aforementioned goals. The results showed that complaints filed against PO1s in PRO6 is in an increasing trend due to low moral values and lack of education or trainings related to the profession.